Structural mechanism for the recognition of E2F1 by the ubiquitin ligase adaptor Cyclin F - Peter Ngoi; Xianxi Wang; Sivasankar Putta; Ricardo F. Da Luz; Vitor Hugo B. Serrão; Michael J. Emanuele; Seth M. Rubin (Proceedings of the National Academy of Sciences, 2025)
Cyclin F, a noncanonical member of the cyclin protein family, plays a critical role in regulating transitions in the cell division cycle. Unlike canonical cyclins, which bind and activate cyclin-dependent kinases (CDKs), Cyclin F functions as a substrate receptor protein within the Skp1–Cullin-F-box E3 ubiquitin ligase complex, enabling the ubiquitylation of target proteins. The structural features that distinguish Cyclin F as a ligase adaptor and the mechanisms underlying its selective substrate recruitment over Cyclin A, which functions in complex with CDK2 at a similar time in the cell cycle, remain largely unexplored. We utilized single-particle cryoelectron microscopy to elucidate the structure of a Cyclin F–Skp1 complex bound to an E2F1 peptide. The structure and biochemical analysis reveal important differences in the substrate-binding site of Cyclin F compared to Cyclin A. Our findings expand on the canonical cyclin-binding motif (Cy or RxL) and highlight the importance of electrostatics at the E2F1 binding interface, which varies between Cyclin F and Cyclin A. These results advance our understanding of E2F1 regulation and may inform strategies for selectively targeting Cyclin F in cancer or neurodegeneration.